Effect of moisture change on water retention behavior of unsaturated silty soil under loading–unloading conditions - Syed Kamran Hussain Shah; Adnan Anwar Malik; Shay Haq; Waqar Ahmad; Umair Ali; Rabia Chaudhry (Discover Civil Engineering)
Abstract Earthen embankments either natural or constructed artificially often comprise of unsaturated soils being considered stronger in terms of compressibility and permeability. However, the internal nomenclature of unsaturated soils due to the presence of air, water, and soil particles makes it more complex while such soils interact with moisture under the circumstances of applied stress history during the earthen structure’s life span. To investigate this behavior, this study is designed to understand the soil–water interaction and quantify the retention behavior during loading and unloading conditions. To serve this idea, custom-designed static compaction tests were carried out under un-drained water and drained air conditions at the applied stress history. The results show application of loading and unloading cycles impact water retention behavior of soil with varying soil water contents. During the initial stages of the loading process, suction increases with decreasing void ratio due to the heterogeneous distribution of water in the soil. However, there is a unique increasing trend in suction at the reloading or wetting phases of the water retention curve for all moisture contents. To examine the impact on the void ratio, the experimental data have been compared with the selected model incorporating suction, void ratio, and degree of saturation for prediction of soil water retention behaviors. The model prediction deviates from the experimental data and shifts away from the model prediction indicating that the loading–unloading sequence coupled with the variation in moisture does affect the soil behavior.